2015
DOI: 10.1021/acs.chemmater.5b00635
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Crystalline Poly(3-hexylthiophene) Solutions Revisited: Role of Time-Dependent Self-Assembly

Abstract: Poly(3-hexylthiophene) (P3HT) in trichlorobenzene solution self-assembles and exhibits liquid crystal ordering when confined to rectangular capillaries. The relative proportion of polymer assemblies increases with time, as determined by UV−vis spectroscopic analysis. Polarized optical microscopy (POM) reveals development of birefringence and monodomainlike long-range ordering. Micro-Raman spectroscopy was used to calculate the orientational order parameters, ⟨P 2 ⟩ and ⟨P 4 ⟩, of the liquid-crystalline P3HT so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
101
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(105 citation statements)
references
References 70 publications
4
101
0
Order By: Relevance
“…It is widely reported that P3HT can undergo a liquid crystal (LC) transition both in the melt and in solutions at room temperature . Incorporation of liquid‐crystalline functionality would induce long‐range ordering that can be reserved and transferred into the condensed film and thus enhance the electric performance of the film greatly .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is widely reported that P3HT can undergo a liquid crystal (LC) transition both in the melt and in solutions at room temperature . Incorporation of liquid‐crystalline functionality would induce long‐range ordering that can be reserved and transferred into the condensed film and thus enhance the electric performance of the film greatly .…”
Section: Resultsmentioning
confidence: 99%
“…Increasing the solubilizing strength (i.e., the size and branching) of the alkyl chains may allow conjugated polymers to be fully soluble in nonpolar solvents. P3HT has shown lyotropic liquid crystallinity in chlorobenzene solutions after extensive aging, whereas the research on the order–disorder transition of P3HT and possible LC formation in toluene solution is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…59 Other polymer waveguide applications include biological 60,61 and environmental 62,63 sensors, as well as non-plasmonic devices for Raman scattering enhancement (e.g., waveguide Raman spectroscopy). 64,65 The theory underlying optical waveguides, both irradiative and leaky, has been presented in several papers.…”
Section: Thin Polymer Waveguide Filmsmentioning
confidence: 99%
“…47,48,[57][58][59][60] Extensive work on P3HT aggregation has been reported by Grey et al 61,62 They classify P3HT films with a ratio of the peak intensities for aggregated and unaggregated chains (I1450 cm -1 /I1470 cm -1 ) greater than 1.5 as highly aggregated chains with correlated planarity and an average intrastack chain-to-chain spacing of approximately 3.8 Å. Table III presents measured parameters for the P3HT carbon-carbon double bond peak at 1450 cm -1 for films prepared in the absence of an external electric field, or with an electric field oriented in the noted directions.…”
Section: Raman Measurementsmentioning
confidence: 99%
“…Very recently, Kleinhenz et al demonstrated that poly(3-hexylthiophene) in trichlorobenzene solution is able to self-assemble and shows liquid crystal ordering when confined to rectangular capillaries [29]. UV-Vis spectroscopy clearly indicated that the relative proportion of poly(3-hexylthiophene) assemblies increases with time; in addition, polarized optical microscopy measurements demonstrated the development of birefringence and monodomain like long-range ordering within the assembled structures.…”
Section: Amphiphilic Self-assembled Lcpsmentioning
confidence: 99%